2015
DOI: 10.1139/apnm-2015-0154
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 8 weeks of motor skill training on cardiorespiratory fitness and endurance performance in children with developmental coordination disorder

Abstract: Interventions based on everyday motor skills have been developed to be effective in children with developmental coordination disorder (DCD). The purpose of the present study was to examine the effects of motor skill training on exercise tolerance and cardiorespiratory fitness in children with DCD. Children were assigned to 3 groups: an experimental training group comprising 14 children with DCD, a control nontraining group comprising 13 children with DCD, and a control nontraining group comprising 14 typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
2
14
0
2
Order By: Relevance
“…The program Partnering for Change ( 56 ) is one such intervention that is currently being tested. While it is complex, and perhaps even overwhelming for health and education professionals to see DCD as more than a motor coordination problem and to focus on prevention of the consequences associated with it, we believe that studies, such as the ones by Caçola et al ( 38 ) and Farhat et al ( 48 ), give some good indications that it is certainly worth trying.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The program Partnering for Change ( 56 ) is one such intervention that is currently being tested. While it is complex, and perhaps even overwhelming for health and education professionals to see DCD as more than a motor coordination problem and to focus on prevention of the consequences associated with it, we believe that studies, such as the ones by Caçola et al ( 38 ) and Farhat et al ( 48 ), give some good indications that it is certainly worth trying.…”
Section: Discussionmentioning
confidence: 98%
“…Several factors that may contribute to poorer fitness in children with DCD have been identified, such as muscular strength, inability to exert maximal force, and variability in rate of power and timing in performing work ( 47 ). A recent study has found that children with DCD perform significantly worse than TD children in the five-jump test, triple-hop distance, the modified agility test, and walking distance ( 48 ). It also appears that the DCD population also shows lower performance in several physiological measurements, as in poorer lung function ( 42 ), earlier exercise fatigue ( 49 ), higher blood concentration, heart rate, respiratory exchange ratio, salivary alpha amylase, lower plain threshold ( 50 ), and reduced baroreflex sensitivity ( 51 ).…”
Section: Physical Health In Dcdmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical approval for the study was granted by the Human Research Ethics Committee of the University of Cape Town (HREC REF: 232/2016) and permission was obtained from the school’s principal. The estimated sample size was determined using previous data [ 31 ]. Based on this information, it was established that 16 participants were needed to detect a difference between pre and post training measures with power of 0.8 and effect size of 0.7.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore reasonable to investigate whether motor skill training delivered in a virtual environment would lead to improvement in skills in real world settings. Even though recent research has demonstrated the occurrence of skill transfer in children with DCD [20], the exact nature of the transfer mechanism is not known.…”
Section: Introductionmentioning
confidence: 99%